Outstanding Texas conservationists announced (Southeast Farm Press, 2020)
Poster Contest and Junior and Senior Essay Contests Conservation Farmer Outstanding Soil and Water Conservation District Conservation Rancher Friend of Conservation Conservation Teacher Wildlife Conservationist The subject for the 2020 Poster Contest was “Where Would We BEE Without Pollinators?" Carli Burger, from Inez and the Jackson Soil and Water Conservation District (SWCD) #336, is this year’s winner. Through these programs, they have implemented an extensive conservation plan consisting of multiple soil and water conservation practices such as conservation tillage, controlled traffic farming, crop rotation, pest management, terraces, grassed waterways, and surface roughening. The Charlesworth Ranch Company incorporates a variety of conservation practices such as Pronghorn friendly fence, brush management, prescribed burning, livestock water pipeline installation, upland wildlife habitat management, and prescribed grazing.